Synergistic effects of antibiotics in combination with essential oils against pathogenic bacterial strains - Mohammad Yaqoob Akhtar, Nabilah; Darnis, Deny Susanti (2014)
The incidence of epidemics due to drug resistant bacteria had posed public health concern. Thus, a novel antibacterial approach to synergize antibiotics in combination with essential oils of selected zingiberaceae plants was chosen in this study to aid in increasing the susceptibility of bacteria. The aim was to evaluate the in vitro interaction between the essential oils and five types of antibiotics against two gram-positive bacteria (Staphylococcus aureus and Bacillus cereus) and two gram-negative bacteria (Esherichia coli and Pseudomonas aeruginosa). Essential oils from rhizomes of Curcuma mangga Val., Zingiber officinale var. rubrum Thelaide and Zingiber zerumbet (L.) Smith were extracted by hydrodistillation. The antibacterial testing employed was Minimum Inhibitory Concentration (MIC) using broth microdilution method. The interaction of essential oils and antibiotics was determined by Fractional Inhibitory Concentration (FIC) using chequerboard technique. Results revealed that essential oil of Curcuma mangga Val. synergized with erythromycin and tetracycline against B. cereus, and with streptomycin against E. coli. Essential oil of Z. officinale synergized with erythromycin and tetracycline against B. cereus and E. coli. Combination with penicillin also produced synergism against E.coli. Essential oil of Z. zerumbet when combined with tetracycline acted synergistically towards S. aureus, B. cereus and P. aeruginosa. Combination with penicillin acted synergistically towards B. cereus, E. coli and P. aeruginosa. When combined with streptomycin, it synergized against S. aureus and E. coli, while with ampicillin it synergized against B. cereus. From the results, all three essential oils exhibit antibacterial properties. Z. zerumbet has the most potent antibacterial property as it produced synergistic effects towards all four types of bacteria.